Cascade Olefin Isomerization/Intramolecular Diels–Alder Reaction Catalyzed by N‐Heterocyclic Carbenes1. (6th April 2014) - Kowalczyk, Marcin; Lupton, David W.
Abstract The addition of an N‐heterocyclic carbene to the carbonyl group of an α, β, γ, δ‐unsaturated enol ester affords a hemiacetal azolium intermediate that enables a cascade olefin isomerization/Diels–Alder reaction, for which mechanistic studies implicate Lewis base catalysis. Preliminary studies into the utility of the products have been undertaken with reductive and oxidative cleavage, giving materials for potential use in complex‐target synthesis.